(untitled) (Applied Biological Research, 2019)
A field survey was conducted in the years 2017 to 2019 for the collection of diseased samples of various crops including Crataegusspecies, from Pulwama and Srinagar districts of Jammu and Kashmir. The leaf and fruit samples of Crataegus songarica showing scab symptoms were collected and brought to the laboratory. During disease monitoring it was noticed that the disease initiated as dark spots on leaves and fruits; and then often covered the entire surface. The mycelium on host was septate, immersed, subcuticular and pale olivaceous; hyphae branched and 2-4 µm wide.On MEA medium the mycelium was septate, branched, interwoven, light pale to olivaceous brown and 3-5 µm wide. The conidia were solitary, fusiform to obclavate having 0- 1 septum (avg. size; 15.64 × 5.76 µm). Based on morphocultural characteristics the fungus was identified as Venturia crataegi. The identity was confirmed by sequencing of ITS region of the pathogen using ITS1 and ITS4 primer. The ITS sequence was submitted to Genbank of NCBI under Accession No. MK478372. For phylogenetic analysis, the sequence was compared with other sequences of Venturia species available at NCBI which showed close relatedness of the present sequence with V. crataegi (Accession No. MH855705.1). The present study forms the first report of crataegus scab caused by Venturia crataegi from India.